PENGARUH KECERDASAN EMOSIONAL DAN KEPUASAN KERJA TERHADAP PERILAKU KEWARGAAN ORGANISASI PADA BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA BARAT DI BANDUNG - Mahri, Nadya; Widjajanta, Bambang; Sumiyati, Sumiyati (Journal of Business Management Education (JBME), 2018)
Aim – The aim of the research was to find out the influence of emotional intelligence, job satisfaction, and organizational citizenship behavior.Design/Methodology/Approach – The research design was cross sectional method. This research employed descriptive approach through explanatory survey method. There were 103 respondents selected through probability sampling. The questionnaires were distributed as the instruments in collecting data from the respondents. The analysis technique used was descriptive technique by using frequency distribution.Findings – Based on the research findings through descriptive analysis, it was found that the emotional intelligence was in the good category by score 9444 and percentage 81.86%, job satisfaction was in high category by score 12198 and percentage 80.56%, and organizational citizenship behavior was in the good category by score 11853 and percentage 82.19%.Originality/value – This research is the basic to understand the emotional intelligence, job satisfaction, and organizational citizenship behavior concept. The difference of the research and  the previous research was in its object aspect, which was West Java Regional Civil Service Agency in Bandung with the observed variables; emotional intelligence, job satisfaction, organizational citizenship behavior by using different theories and references from previous research.